State “Currencies” and the Transition to the U.S. Dollar: Reply—Including a New View from Canada - Grubb, Farley W (American Economic Review, 2005)
State "Currencies" and the Transition to the U.S. Dollar: Reply-Including a New View from Canada by Farley W. Grubb. Published in volume 95, issue 4, pages 1341-1348 of American Economic Review, September 2005